Typhoid fever - Meiring, JE; Khanam, F; Basnyat, B; Charles, RC; Crump, JA; Debellut, F; Holt, KE; Kariuki, S; Mugisha, E; Neuzil, KM; Parry, CM; Pitzer, VE; et al. (Springer Nature, 2023)
Typhoid fever is an invasive bacterial disease associated with bloodstream infection that causes a high burden of disease in Africa and Asia. Typhoid primarily affects individuals ranging from infants through to young adults. The causative organism, Salmonella enterica subsp. enterica serovar Typhi is transmitted via the faecal–oral route, crossing the intestinal epithelium and disseminating to systemic and intracellular sites, causing an undifferentiated febrile illness. Blood culture remains the practical reference standard for diagnosis of typhoid fever, where culture testing is available, but novel diagnostic modalities are an important priority under investigation. Since 2017, remarkable progress has been made in defining the global burden of both typhoid fever and antimicrobial resistance; in understanding disease pathogenesis and immunological protection through the use of controlled human infection; and in advancing effective vaccination programmes through strategic multipartner collaboration and targeted clinical trials in multiple high-incidence priority settings. This Primer thus offers a timely update of progress and perspective on future priorities for the global scientific community.